Desarrollo de una aplicación móvil para la oferta de servicios y productos identificando las preferencias del cliente mediante una red neuronal multicapa en la Asociación Interprofesional de maestros y operarios del cantón San Cristóbal en la provincia de Galápagos. - Cujilan Oña, Dayana Fernanda (2021)
The Interprofessional Association of Teachers and Workers of San Cristobal Canton was created in 1998 and currently has 39 members who need to promote their services and/or products, for which they have resorted to traditional advertising media, including commercials on radio stations, which have been insufficient to adequately reach potential clients. It is also important to mention that radio advertising represents a considerable economic investment that could be optimized through the use of information and communication technologies (ICTs) to offer in a structured manner each of the services offered without limitations of time or space, which is expected to increase the number of users in general. It is proposed the development of a mobile environment application with autonomous capabilities to identify customer preferences through the application of a multilayer neural network that contributes to the supply of products and services of the Interprofessional Association of Teachers and Workers of San Cristobal Canton where it has been shown that it is desirable that people have a digital medium where they can access in a comfortable, easy and practical way to a catalog of services and products provided by the aforementioned association that is a beneficiary of this technological proposal.